Om digteren Grundtvig - Larsen, Finn Stein (Grundtvig-studier, 1984)
On Grundtvig the Poet By Finn Stein LarsenA detailed review of Grundtvig the Poet by the poet and critic Poul Borum (284 pages, Gyldendal, 200 Dkr.). The reviewer is himself a critic on a daily paper and like Borum has “ a passion for Grundtvig and modern poetry” . Stein Larsen praises the treatment of New Year's Morn and of the hymns. Borum is “privy to” Grundtvig’s thoughts and has “a willing ear for what he says” . One particular feature he draws attention to in Grundtvig is a “ continually fresh process of name-giving” . Drawing on the critic Paul de Man he quotes Mallarmé and Stefan George. Grundtvig gives the words a purer meaning and can find his own names for things.The reviewer stresses that “ Grundtvig’s imagery is also and always con138 crete” . Of The Easter Lily (Paaske-Lilien) he writes, “ Until the peasant flower stands as a reality in a room, as part of the furniture in his study, we cannot see what is is meant to mean.” And later: “ If Eliot had read Grundtvig’s poetry he would have found an inexhaustible supply of objective correlatives.” Stein Larsen agrees with Borum that “ self-validating and original namegiving” in Grundtvig runs parallel with a complex wealth of meaning, and he regards the demonstration of this as Borum’s most significant merit. “ All his interpretations... swing between mythologizing, stylizing, ideologizing emblematics on the one hand, and the recognized gesture and the simple namegiving on the other” . In a poetic pantheon of classic modern writers Borum, instead of making him “merely contemporary” , places Grundtvig in many surprising contexts together with great modern poets: Blake, Coleridge, Yeats, Wallace Stevens, Hölderlin, Mallarmé, Marianne Moore and T. S. Eliot.In his chapter on the hymns Borum is critical of hymnologists, who are “ sometimes hasty and brief... though only seldom unreasoned” ... “ Only Magnus Stevns and Christian Thodberg are allowed through.” But Stein Larsen also sees the chapter on the hymns as “an incursion into the area that calls for further treatment” . On the other hand he does not think “one should ignore Borum’s contribution to Grundtvig’s homiletics” . And in general he considers the accounts “borne up by a long, energetic breath” . But he cannot understand how Borum could write at one point that “ Grundtvig is friendless” ; and he also criticizes the portrait of P. G. Lindhardt as inconsistent. Nor does he accept Borum’s series of impressive trinities: Creed, ministry, song of praise; Body, soul, spirit; Father, Son, Holy Spirit. There is a further lack of concern in Borum for “ the key years, 1810, 1824, and 1832” , which Stein Larsen attributes to haste. He regrets that Borum has not achieved a comprehensive view, for “he is the man who could actually do so,” says Stein Larsen.